Differential diagnosis of a solitary pulmonary nodule of the lung on the grounds of selected laboratory tests and radiological examination - Szlachcińska, Aleksandra; Kozak, Józef (Contemporary Oncology/Współczesna Onkologia, 2011)
Objective : To present in detail the diagnosis of solitary pulmonary nodule and especially evaluation of: • clinical data, • analysis of radiological images, • selected laboratory tests. Material and methods : There were 50 patients – 31 men and 19 women at the mean age 58.7 ±11.4 years old who underwent surgical treatment because of a solitary pulmonary nodule. Interview, physical examination, computed tomography, bronchoscopy, spirometry, and laboratory tests needed for the operation were performed in all these patients. Additionally LDH, fibrinogen, ESR, and the tumour markers CEA, Ca 15-3, Ca 19-9, NSE, SCC, and Cyfra 21-1 were measured from the blood sample collected during admission. Results : Malignant tumour was diagnosed in 24 patients, benign in 26. There is a significant difference between patients with malignant and nonmalignant tumours in age (54.46 years vs. 63.33 years), size of the tumour in the lung scan of chest CT (1.53 cm vs. 1.91 cm) and location (lower right lobe vs. upper right lobe). There is no significant difference between type of tumour and sex, clinical symptoms and laboratory tests. Conclusions : 1. The risk factors of malignancy in patient with solitary pulmonary nodule are: • age ≥ 56.5 years, • size of the tumour in the lung scan of chest CT ≥ 1.45 cm, • location in upper right lobe. 2. LDH, fibrinogen, ESR, and the tumour markers CEA, Ca 15-3, Ca 19-9, NSE, SCC, and Cyfra 21-1 are not useful in differential diagnosis of solitary pulmonary nodule.